Successful Treatment of Fluconazole-Resistant Oropharyngeal Candidiasis by a Combination of Fluconazole and Terbinafine - Ghannoum, Mahmoud A. (American Society for Microbiology, 1999)
Increasing incidence of resistance to conventional antifungal therapy has demanded that novel therapies be introduced. Recent in vitro studies have shown that combinations involving azoles and allylamines may be effective in inhibiting fluconazole-resistant fungi. In this report, we describe the case of a 39-year-old woman who presented with white patches on her buccal mucosa, tongue, and palate with a bright erythematous erosive base. A fungal culture revealed Candida albicans. The patient failed to respond to the initially prescribed fluconazole therapy. Failure of therapy can be attributed to a developed resistance to fluconazole from the patient’s intermittent use of this antifungal agent at varying dosages for the preceding 2 years due to a diagnosis of onychomycosis. In vitro testing of the culture from the patient showed elevated MICs of fluconazole, itraconzole, and terbinafine (MICs were 32, 0.5, and 64 μg/ml, respectively). Our goal was to combine therapies of fluconazole and terbinafine in an attempt to clear the fungal infection. Impressively, this combination resulted in the clearing of the clinical symptoms and the patient has successfully been asymptomatic for more than 12 months posttreatment.